Reaktualisasi Dakwah Konvensional di Tengah Ekosistem Digital: Analisis Tantangan, Peluang, dan Transformasi di Platform Media Sosial - Hamama, Syifa (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2025)
This article explores the challenges faced by conventional da'wah when confronted with the dynamics of digital communication on social media. The core issue identified is the limited ability of traditional da'wah approaches to engage younger audiences who are more responsive to interactive and algorithm-driven communication formats. The purpose of this study is to evaluate the relevance of classical da'wah methods, map the emerging challenges in the age of social media, and identify transformative opportunities that enable da'wah to remain effective within the digital landscape. This article employs a qualitative analytical method based on literature review, analysis of digital media contexts, and examination of digital communication theories. The findings indicate that the most effective strategy lies in integrating conventional da'wah with digital approaches. The relevance of traditional da'wah becomes even more pronounced when strategically combined with the sophistication of social media. Conventional da'wah serves as an anchor that preserves depth and authenticity, while digital da'wah expands its reach to wider publics, especially young people. Through this combination, da'wah can remain relevant, adaptive, and transformative amid the significant changes brought about by the digital age.